COMMUNITY SERVICE EVALUATION OF TOURISM MARKETING TRAINING AT STATE VOCATIONAL SCHOOL 2 SEKOTONG - Sutarini, Ida Ayu; Maulida, Novita; Amy, Najamuddin (Universitas Mataram, 2024)
Community service (PkM) is one of the Tri Dharma programs of higher education institutions that must be carried out by every lecturer. The Communication Studies Program at Unram conducted a community service activity on Saturday, May 4, 2024, at SMK Negeri 2 Sekotong titled